Coronary arteries in fibromuscular dysplasia. 3-Dimensional coronary CT, case-control study. The ARCARDIA-POL BIS study. (25th November 2020) - Kruk, M; Szkamruk, K; Adlam, D; Persu, A; Pappaccogli, M; Van Der Niepen, P; Kepka, C; Januszewicz, M; Pregowski, J; Skowronski, J; Kabat, M; Warchol-Celinska, E; et al.
Abstract: Background: Fibromuscular dysplasia (FMD) is a non-atherosclerotic arterial disease characterized by the presence of string-of-beads or focal stenosis. Other FMD-related lesions include arterial dissections, aneurysms, and tortuosity. However, limited data are available on the involvement of coronary arteries in pts diagnosed with "extra-coronary" FMD. Purpose: To examine FMD-related coronary artery involvement, coronary artery lesions and coronary tortuosity in patients with a diagnosis of "extra-coronary" FMD. Methods: In a case control study we enrolled 103 (age 45.7±13.2, 82 women) consecutive patients with a diagnosis of FMD, in whom atherosclerotic coronary artery disease was excluded on the basis of coronary CTA, and 96 (age 47.3±12.2, 75 women) sex- and age-matched controls without coronary atherosclerosis based on CTA imaging (Siemens Force 2x192 scanner). Detailed analysis of coronary arteries was assessed, with detailed analysis of arterial tortuosity, defined as curves >30 OR >45 OR >90 degrees. Tortuosity Index (TI) was defined as number of curves x artery length (centerline) / vector artery start-end. Each arterial tortuosity evaluation was performed per coronary segment AND per artery. Size (area, length) of coronary arteries was also measured. Results: Intravessel symmetry sign and cork-screw sign were more common in arteries of FMD patients than in controls (5.4% vs 1.3%, p<0.001; 1.2% vs 0%, p=0.03, respectively). Number of arterial curves and TI of LAD, LCx and RCA were higher in FMD patients than in controls (arterial curves: p<0.01 for all arteries – TI: 14.9 vs 8.5 for LAD, 9.8 vs 6.6 for LCX, and 11.2 vs 6.6 for RCA; p<0.001 for all arteries). According to the segmental analysis, AUC under the ROC curve indicated the highest value for prediction of FMD for the number of curves (>30 degrees) (0.777; 95% CI:0.713 to 0.833) or TI (0.794; 95% CI: 0.731 to 0.848), both in distal LAD. For the distal LAD indices, the best sensitivity and specificity values were for ≥4 curves (sens. 74%, spec. 72%) or for a TI >5.6 (sens. 55%, spec. 94%), respectively. These predictive values were confirmed after correction for potential confounders. Interestingly, neither proximal LAD or proximal LCx number of curves or TI were related to FMD. No difference was found in terms of areas of coronary arteries between FMD patients and controls, with the only exception of LM (20.8±6.6 vs 17.9±5.8, p=0.002). Mean coronary artery lenght was significantly different between controls and patients with FMD (respectively LM 8.4±4.2 vs 9.8±4.5, p=0.022; LAD 117.8±28.6 vs 109.1±30.2, p=0.042; LCx 85.2±43.9 vs 62.9±31.4, p<0.001; RCA 104.2±24.4 vs 115.7±25.8, p=0.002). No coronary aneurysms, ectasias or dissections were found in the examined cohort. Conclusions: Distal and not proximal coronary arterial tortuosity is related to FMD. Coronary tortuosity defined as 4 distal LAD curves or a TI >5.6 are highly specific for FMD. Funding Acknowledgement: Type of funding source: None